Determination of the Band Broadening Function in Size Exclusion Chromatography with Light-scattering Detection - Yossen, Mariana Matilde (2012)
This work describes the determination of the band broadening function (BBF) in a size exclusion chromatograph fitted with 2 mixed-gel columns, a light scattering (LS) detector, and a differential refractometer (DR). The raw data were the chromatograms of 4 narrow polystyrene standards. First, the interdetector volume shift was indirectly estimated from its upper and lower limiting values. Then, for each of the standards, their ‘‘local’’ BBFs were estimated by application of an existing theoretical method. Each local BBF is an assumed elution-volume invariant in the narrow ranges of the analyzed standards and is represented by an exponentially-modified Gaussian of standard deviation rBB and exponential decay sBB. Finally, a ‘‘global’’ BBF (valid for the complete fractionation range) was interpolated from the local BBF parameters. For increasing elution volumes, the global BBF exhibits an increasing rBB and a decreasing sBB. In addition, the asymmetry factor [sBB=rBB] and the global variance [r2 BB þ s2 BB] both decrease with elution volume.